2021
DOI: 10.1029/2021gh000528
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Forest Fire Activity Changes Over the Central India Domain Using Satellite Observations During 2001–2020

Abstract: Forest fire is an increasingly common phenomenon that affects almost all forest types and biomes on earth, largely causing global to regional changes in the air quality, radiation budget, land-atmosphere interactions, nutrient cycles, and ecological balance (Bowman et al., 2011;Cochrane, 2009;Giglio et al., 2016). Recurrent fires also pose considerable threat to nearby residents who often suffer from cardiovascular and respiratory diseases such as asthma, chronic bronchitis, and emphysema. In cases of massive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Jain et al ( 2020) identified Delhi's annual average levels of OC and EC as 15.73 ± 12.72 and 7.31 ± 6.17 µg m −3 , respectively, for PM 2.5 . Jain et al (2021) also noticed PM 2.5 bound OC and EC levels as 15.09 ± 8.72 and 6.54 ± 3.27 µg m −3 , respectively, in Varanasi. While in Kolkata, OC and EC levels were observed as 17.91 ± 9.72 and 9.43 ± 4.11 µg m −3 , respectively.…”
Section: Level Distribution Of Carbonaceous Componentsmentioning
confidence: 61%
“…Jain et al ( 2020) identified Delhi's annual average levels of OC and EC as 15.73 ± 12.72 and 7.31 ± 6.17 µg m −3 , respectively, for PM 2.5 . Jain et al (2021) also noticed PM 2.5 bound OC and EC levels as 15.09 ± 8.72 and 6.54 ± 3.27 µg m −3 , respectively, in Varanasi. While in Kolkata, OC and EC levels were observed as 17.91 ± 9.72 and 9.43 ± 4.11 µg m −3 , respectively.…”
Section: Level Distribution Of Carbonaceous Componentsmentioning
confidence: 61%
“…Badarinath et al ( 2011 ) reported intense forest fire episodes in Kerala during the year 2004, which started in January and increased even more in February and March due to a decrease in rainfall and high temperatures than normal years. Jain et al ( 2021 ) observed the occurrence of increased forest fires associated with severe heatwave, drought and strong El Niño during 2015 July–January and 2018 February–June over central India. Chand et al ( 2006 ) found that the spatial variation in peak fire seasons was attributed to the varying forest types and climatic conditions over the Indian subcontinent.…”
Section: Resultsmentioning
confidence: 99%
“…From a heat stress perspective, the triple whammy of unabated globally rising temperatures, increasing UHIIs (or SUHIIs), and increasingly frequent prolonged heatwaves of extreme severity during pre-monsoon (MAM) season is of utmost concern in cities of India (World Health Organization (WHO), 2020; India Meteorological Department (IMD), 2021a; Jain, 2021bJain, , 2022Jain et al, 2021). A number of factors such as urban area (e.g., impervious surface area, built-up density, building heights, etc.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Studies have found a significant increase in frequency, severity and intensity of climate extremes e.g., droughts, heatwaves, wildfires, hurricanes, and floods; which likely will exacerbate life and property losses in the future, along with causing food shortages and an increase in disease causing pathogens (Robinson, 2001;Black et al, 2004;Li et al, 2009;Dai, 2011;Intergovernmental Panel on Climate Change (IPCC), 2012Mishra et al, 2017;Hawcroft et al, 2018;Bisht et al, 2019;Hasegawa et al, 2021;Jain, 2021aJain, , 2022Jain et al, 2021;Climate Transparency, 2022). Unlike the other climate extreme events, heatwave caused fatalities are not immediately obvious, but lead the weather-related cause of deaths globally (Hajat and Kosatky, 2010;Peterson et al, 2013;World Health Organization (WHO), 2020).…”
mentioning
confidence: 99%